No Way of Knowing : Crime, Urban Legends, and the Internet. - Donovan, Pamela (American popular history and culture (Routledge (Firm)), 2003)
This book examines both 'old media' treatment of crime legends: news reports, fictional film and television depictions, as well as 'new' media interactive discussions of them via the Internet and electronic mail.